The impact of caloric information on college student's fast food purchasing intentions - Zigmont, Victoria A; Bulmer, Sandra Minor (American journal of health education, 2015)
Background: Fast food establishments are available on many college campuses and, as a result, many students consume foods that are high in calories and contribute to unhealthy weight gain. Purpose: This study measured college students' knowledge of the calorie content for fast food items and whether the provision of calorie information for those foods influenced their future purchasing intentions. Method: Randomly selected undergraduate college students (N = 201) completed an online survey that measured baseline knowledge of calorie content for a fast food item and intention to purchase that item in the future. After provision of accurate calorie information, students were posttested for intention to purchase that item in the future. Results: The majority of students underestimated calorie content for fast food items. After receiving accurate calorie information, those who initially underestimated calorie content were significantly more likely to change their intention to purchase that food item in the future. Discussion: Many college students are interested in avoiding high-calorie fast food items but are uninformed about calorie content. Translation to Health Education Practice: Colleges should provide calorie information for fast food items at the point of purchase so that students can make informed decisions that will promote their health. © 2015, Copyright © SHAPE America.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/080-184-250-213-713 tex.type: [object Object]
Keywords: dept.hhs; dept.pch

Do adult medicaid enrollees prefer going to their primary care provider's clinic rather than emergency department (ED) for low acuity conditions? - Capp, Roberta; Camp-Binford, Meredith; Sobolewski, Sarah; Bulmer, Sandra; Kelley, Lauren (Medical Care, 2015)
Background: The rates of annual visits for adult Medicaid enrollees to the emergency department (ED) are increasing. Many programs throughout the country are focused on engaging patients in the use of their primary care providers (PCP) rather than the ED for low acuity conditions. It is unclear, however, the proportion of patients who are willing to use primary care services rather than the ED if they are given the choice. Methods: Cross-sectional study of adult Medicaid enrollees (18 y and older) presenting to a large, urban, academic ED from June to August 2012 with a low acuity condition was performed. We excluded patients who did not have a PCP or active Medicaid insurance. Our primary goal was to determine the proportion of patients who prefer to use the ED, rather than their PCP clinic, if an appointment was immediately available. Our second goal was to understand why patients would prefer ED over PCP care. Results: A total of 150 patients agreed to complete the survey, and 95 (63.3%) met our inclusion criteria. Forty-three patients (45.3%) stated preferring to use their PCPs rather than the ED if an appointment was available at that time. Thirteen (48.1%) cited that the ED had more technology or specialty care services available when compared with their PCP's clinic, 8 (15.4%) were in significant pain, and 6 (11.5%) felt the care they received in the ED was better than what they would receive in their PCP clinic. Conclusions: Our study shows that a little less than half of adult Medicaid enrollees presenting to the ED with low acuity conditions would have preferred to use their PCP rather than the ED, if an appointment had been immediately available.
11 citations (Crossref) [2023-10-31] tex.eissn: 1537-1948 tex.unique-id: ISI:000354726500010
Keywords: Academic Medical Centers; Adult; Article; Continental Population Groups; Cross-Sectional Studies; Emergency Service; Hospital; Female; Health Services Accessibility; Humans; Male; Medicaid; Middle Aged; Patient Preference; Patient Satisfaction; Primary Health Care; United States; Urban Population; adult; ancestry group; cross-sectional study; dept.hhs; emergency department; emergency health service; emergency ward; female; health care availability; health care delivery; health service; health survey; human; major clinical study; male; medicaid; middle aged; pain; patient preference; patient satisfaction; primary care clinic; primary health care; primary medical care; priority journal; statistics and numerical data; technology; university hospital; urban population

Adolescents' and Young Adults' Perceptions of Electronic Cigarettes for Smoking Cessation: A Focus Group Study. - Camenga, Deepa; MD, MHS; Cavallo, Dana; Kong, Grace; Morean, Meghan; PhD 2, 3; Connell, Christian; Simon, Patricia; Bulmer, Sandra; Krishnan-Sarin, Suchitra (Nicotine Tob Res, 2015)
Introduction: Research has shown that adults perceive that electronic cigarettes (e-cigarettes) are effective for smoking cessation, yet little is known about adolescents and young adults' perceptions of e-cigarettes for quitting cigarette smoking. This study describes middle, high school, and college students' beliefs about, and experiences with, e-cigarettes for cigarette smoking cessation., Methods: We conducted 18 focus groups (n = 127) with male and female cigarette smokers and nonsmokers in 2 public colleges, 2 high schools, and 1 middle school in Connecticut between November 2012 and April 2013. Participants discussed cigarette smoking cessation in relation to e-cigarettes. Verbatim transcripts were analyzed using thematic analysis., Results: All participants, regardless of age and smoking status, were aware that e-cigarettes could be used for smoking cessation. College and high school participants described different methods of how e-cigarettes could be used for smoking cessation: (a) nicotine reduction followed by cessation; (b) cigarette reduction/dual use; and (c) long-term exclusive e-cigarette use. However, overall, participants did not perceive that e-cigarette use led to successful quitting experiences. Participants described positive attributes (maintenance of smoking actions, "healthier" alternative to cigarettes, and parental approval) and negative attributes (persistence of craving, maintenance of addiction) of e-cigarettes for cessation. Some college students expressed distrust of marketing of e-cigarettes for smoking cessation., Conclusions: Adolescent and young adult smokers and nonsmokers perceive that there are several methods of using e-cigarettes for quitting and are aware of both positive and negative aspects of the product. Future research is needed to determine the role of e-cigarettes for smoking cessation in this population., (C) Copyright Oxford University Press 2015.
51 citations (Crossref) [2023-10-31] Place: (C) Copyright Oxford University Press 2015.
Keywords: Adolescent; Age Factors; Article; Asian; Black person; Caucasian; Connecticut; Electronic Cigarettes; Female; Focus Groups; Health Knowledge; Attitudes; Practice; Hispanic; Humans; Longitudinal Studies; Male; Marketing; Nicotine; Schools; Smoking; Smoking Cessation; Students; Tobacco Use Disorder; United States; Universities; Young Adult; adolescent; adult; age; age distribution; attitude to health; awareness; clinical effectiveness; clinical trial; college student; comparative study; controlled study; dept.pch; electronic cigarette; female; high school student; human; information processing; longitudinal study; male; marketing; middle school student; multicenter study; nicotine; parental approval; parental attitude; prevention and control; priority journal; procedures; psychology; qualitative analysis; school; semi structured interview; sex difference; smoking; smoking cessation; smoking habit; social marketing; social norm; student; tobacco dependence; university; withdrawal syndrome; young adult